Corporate Governance Scorecard 2009 : Baseline Report - International Finance Corporation; Global Corporate Governance Forum; State Securities Commission of Vietnam (International Finance Corporation, Washington, D.C., 2017)
During the past decade, the Vietnamese securities market has made large strides and secured a firm position as a channel for mid-term and long-term capital mobilization for national economic development. However, the management and regulations of an emerging securities market have posed numerous challenges to the national securities regulator - the State Securities Commission (SSC). In its role to establish, regulate, and supervise the securities market applying international corporate governance (CG) standards and best practices, the SSC has taken the initiative in obtaining assistance from international organizations to help establish more transparent and efficient securities market operations. Therefore, the SSC and International Finance Corporation (IFC) are partners in several initiatives to improve CG in Vietnam. The development of the Vietnam CG scorecard and the associated scorecard report is part of this wider CG project to assist the regulator to enhance the application of international CG standards and practices. This initial survey of CG practices in Vietnam is the baseline review of CG in Vietnam. It encompasses a survey of some 100 companies listed on the Hanoi and the Ho Chi Minh stock exchanges, which together represent more than 90 percent of the combined market capitalization of these exchanges. The scorecard report is expected to: provide a standardized, systematic framework by which regulators and investors may assess the CG of a company and the overall level of CG in Vietnam; enable a company to assess the quality of its CG and to stimulate companies to enhance their practices; provide a systematic way to analyze CG across industries to assist improvements in CG practices; assist regulatory groups to identify strengths and weaknesses in CG regulations and practices, leading to further reforms; and be available to support the raising of awareness and understanding of good CG practices. The scorecard is a tool that regulators, companies, investors, and the marketplace can use to focus on CG and it will provide a common metric and language on CG in Vietnam. It opens up opportunities for dialogue on CG and allows for Vietnamese institutions to take appropriate steps to address the CG issues highlighted by the findings of the report.